Ultra-Processed Food Consumption and Its Impact on Nutritional Status of Preschool Children in Urban Areas - Wulan, Anisa Nur; Rosdiana, Delita Septia; Fauza, Ahdiyatul; Santanu, Ayu Mutiara (Indonesian Journal of Human Nutrition, 2026)
Due to imbalanced dietary intake during a critical period of growth, preschool children are vulnerable to nutritional issues. This study aimed to examine the relationship between ultra-processed food (UPF) consumption and the nutritional status of preschool children in urban areas. A cross-sectional study design was carried out with 60 kindergarten children in the working area of the Pasirkaliki Health Center. Nutritional status was assessed using anthropometric measurements, and dietary intake and UPF consumption were evaluated using SQ-FFQ and two 24-hour food recalls. Data were analyzed using univariate and bivariate methods with SPSS version 27.0. According to the findings, 79.3% of children had normal nutritional status, whereas 10.3% were classified as overweight and 5.2% as obese. A total of 41.7% of children were categorized as having a high frequency of UPF consumption. Statistical analysis indicated significant relationships between energy intake (p=0.008), protein intake (p=0.010), and fat intake (p=0.001) and nutritional status. A significant relationship was found between the frequency of UPF consumption and nutritional status (p=0.010). In short, frequent consumption of UPF contributes to a high risk of overnutrition, and parental awareness and nutrition literacy are needed in shaping healthy eating patterns to prevent long-term health impacts.